155 Sociodemographic characteristics and environmental features of mass-shooting locations in ten US cities. (5th May 2020) - Ross, Sharmaine; Forman, Steven; Morrison, Christopher; Jacoby, Sara F; Dong, Beidi; Maher, Zoë; Beard, Jessica H
Abstract : Statement of Purpose: Mass-shootings involving ≥ 4 people injured or killed occur frequently in cities in the United States. However, little is known about the places affected by mass-shootings. We aimed to describe the sociodemographic characteristics and environmental features of mass-shooting locations in US cities. Methods: Using Gun Violence Archive data, we identified all mass-shootings in the 10 US cities with the highest homicide rates from 2014–2017 (n=214). We geocoded the event locations and used American Community Survey estimates to describe the sociodemographic characteristics of mass-shooting block groups with 6 indicators of structural disadvantage. We compared mass-shooting block group sociodemographic characteristics with each city's characteristics overall using Students t-tests. We assessed the environmental features of mass-shooting locations using Google Street View to code 60 elements of the visible environment. Results: Compared to overall city demographics, mass-shooting block groups had significantly higher rates of poverty (28.0% vs. 35.1%; p=0.004), unemployment (8.2% vs. 10.1%; p=0.005), Black residents (47.5% vs. 70.0%; p=0.012) and renter occupied units (53.0% vs. 57.9%; p=0.027), while percentage of college attendees/graduates (55.8% vs. 30.2%; p<0.0001), and median household income (37, 302 vs. 31, 313; p=0.009) were significantly lower in mass-shooting block groups. Sixty-four percent of mass-shootings occurred in residential locations, and most locations demonstrated indicators of physical disorder. Average building conditions were graded as moderate; 37.4% of locations had buildings with broken/boarded windows and 78.3% had moderate to extreme littering. 94.3% and 93.1% of locations had no parks or playgrounds respectively. Conclusions: Mass-shootings in urban environments tend to occur in residential locations with significant structural disadvantage. The built environment of mass-shooting locations is characterized by blighted buildings and limited green spaces. Contributions to Injury and Violence Prevention Science: Discourse about mass shootings often excludes urban spaces. Structural disadvantage and modifiable environmental features are key targets for mass-shooting prevention in US cities.